Animal performance and sward characteristics of piatã palisade grass pastures subjected to different grazing intensities - Nantes, Nayana Nazareth; Euclides, Valéria Pacheco Batista; Montagner, Denise Baptaglin; Lempp, Beatriz; Barbosa, Rodrigo Amorim; Gois, Phillippe Oliveira de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the nutritive value, sward structure, and animal performance of steers on piatã palisade grass pastures (Urochloa brizantha, cultivar Piatã), managed at 15, 30, and 45 cm sward heights, under continuous stocking. A randomized block design, with two replicates and three sward heights, was used. Sward height was measured twice a week, and the stocking rate was adjusted. Monthly, the pastures were sampled and the animals were weighted. There was no difference in the nutritive value of the pastures managed with different heights. The average daily gain of 650 g per steer was similar among the different sward heights. The stocking rate was lower for the pasture managed at 45 cm (2.4 AU ha‑1), intermediary for the one with 30 cm (3.1 AU ha‑1), and higher for the one managed at 15 cm (3.8 AU ha‑1), resulting in greater gain per area for the pastures managed at a height of 15 cm (1,050 kg ha‑1) and 30 cm (910 kg ha‑1) than for the one managed at 45 cm (635 kg ha‑1). Piatã palisade grass shows great flexibility under continuous stocking and can be managed between 15 and 45 cm sward height.